The Urgency of The Entrepreneurial Spirit among Young Generation - Klarista Yumaristi Ngode; Yosefa Payogi Jontari Putra; Enike Tje Yustin Dima (Yayasan Pendidikan Islam Al-Matani, 2026)
This article examines the urgency and importance of entrepreneurship education to overcome unemployment and poverty in Indonesia. One of the population problems in Indonesia is the still high unemployment and poverty rates. Various efforts to reduce unemployment and poverty have also been made by the Indonesian government, but the results have not been significant enough. Therefore, various efforts are needed to develop the entrepreneurial spirit among the Indonesian people. One of the efforts is to promote and organize entrepreneurship education. The development of digital technology has brought significant transformation in the world of entrepreneurship, opening up more inclusive and flexible business opportunities. This article discusses the importance of fostering an entrepreneurial spirit in the digital era, especially among the younger generation who actively use technology. An entrepreneurial spirit that includes the courage to take risks, the ability to innovate, and the readiness to adapt is key to facing modern business challenges.